The Relationship between Self-esteem and Academic Achievement in Pre-clinical and Clinical Medical Students - vida Sepahi; Elham Niroumand; Farahnaz Keshavarzi; Ahmad Khoshay (Babol University of Medical Sciences, 2015)
BACKGROUND AND OBJECTIVE: The relationship between self-esteem and academic achievement is regarded by many educators as a well-established fact. This belief has been often invoked in order to argue against the provision of ability grouping for gifted students. The aim of this study was to determine the relationship between self-esteem and academic achievement in pre-clinical and clinical medical students in Kermanshah University of Medical Sciences. METHODS: In this descriptive-analytic and cross-sectional study, 259 pre-clinical and clinical medical students were randomly selected through a stratified sampling method in Kermanshah University of Medical Sciences. The data gathering instrument included Cooper-Smith self-esteem inventory. The results were analyzed using descriptive statistics, Spearman correlation coefficient, Chi-Square, independent sample t-test, and Mann-Whitney test. FINDINGS: Results showed that the students' mean scores in self-esteem was 35.90±6.87. 149 students (57.5%) had high self-esteem. There was a significant correlation between the level of self-esteem and academic achievement (P=0.03, χ2=4.7). CONCLUSION: Students with higher self-esteem had a better academic achievement compared with those who had lower self-esteem. Thus, it may be possible to promote academic achievement by improving self-esteem through appropriate methods, but due to cultural differences and fast changes of factors during the time, not a single factor can be stated as the overall rule